MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMP PADA MATERI SISTEM RESPIRASI PADA MANUSIA MELALUI MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS - Tati Yuniarti (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
IMPROVING THE ACTIVITY AND LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS ON LESSONS OF HUMAN RESPIRATION SYSTEMS THROUGH STUDENT TEAMS ACHIEVEMENT DIVISION MODELSThis study aims to improve learning outcomes, see the improvement of learning outcomes, measure the increase in student learning outcomes in the subject matter of Human Respiration System Science through the application of Student Teams Achievement Divisions (STAD) model. This research is a Classroom Action Research by providing action on research subjects in two learning cycles in class VIII.H SMPN 5 Bogor Academic Year 2019/2020. The results of this study indicate that using the Student Teams Achievement Divisions model can be a fun learning variation for students so that it is proven to improve student learning outcomes. Before using the Student Teams Achievement Divisions model in the division it became an average and completeness of learning 62.10 and 34.38% the increase occurred after using the Student Teams Achievement Divisions model in the division to 79.34 and 68.75% in cycle I, and it occurred increased again to 87.26 and 100% in cycle II. The results showed that using the Student Teams Achievement Divisions model in the division which was adapted to learning materials that could create a pleasant atmosphere so that there was an increase in student learning outcomes. Therefore, researchers suggest that the Student Teams Achievement Divisions model be socialized to be used as an alternative in science learning in schools within the Bogor City Education Office.